1996
DOI: 10.1007/bf02207280
|View full text |Cite
|
Sign up to set email alerts
|

An ammonium pulse inhibits fluid secretion

Abstract: Exposing perfused mandibular salivary glands to a 5-min pulse of NH4Cl almost totally inhibited fluid secretion evoked by acetylcholine. Recovery from exposure to 0.5 mM NH4Cl occurred within 10 min, but after exposure to 20 mM NH4Cl recovery was not complete even after 30 min. The inhibition could not be explained by changes in intracellular pH as there was no acidosis measurable after the 0.5 mM NH4Cl pulse. NH4Cl did not inhibit intracellular calcium release by acetylcholine so that receptor inhibition coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…However, our experimental setup virtually rules this out, because we measured NBC activity after a NH 4 ϩ prepulse and preincubation in Na ϩ -free, DMA-containing solution. Several groups (25,31,54,57) have found strong inhibition of anion secretion after exposure to NH 4 ϩ in different secretory epithelia. In some of these studies, the inhibitory effect could be demonstrated as long as 30 min after NH 4 Cl exposure (25,54).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our experimental setup virtually rules this out, because we measured NBC activity after a NH 4 ϩ prepulse and preincubation in Na ϩ -free, DMA-containing solution. Several groups (25,31,54,57) have found strong inhibition of anion secretion after exposure to NH 4 ϩ in different secretory epithelia. In some of these studies, the inhibitory effect could be demonstrated as long as 30 min after NH 4 Cl exposure (25,54).…”
Section: Discussionmentioning
confidence: 99%
“…Several groups (25,31,54,57) have found strong inhibition of anion secretion after exposure to NH 4 ϩ in different secretory epithelia. In some of these studies, the inhibitory effect could be demonstrated as long as 30 min after NH 4 Cl exposure (25,54). To verify this for carbachol stimulation in the murine colon, we measured I sc in Ussing chambers using the murine colonic mucosa after a NH 4 Cl prepulse and DMA preincubation.…”
Section: Discussionmentioning
confidence: 99%
“…In perfused rabbit mandibular glands, the weak base NH 4 Cl had dramatic inhibitory effects upon ACh‐evoked fluid secretion (Lau, Donohue & Case, 1996). Even at concentrations as low as 0.5 mM, NH 4 Cl totally inhibited fluid secretion.…”
Section: Discussionmentioning
confidence: 99%
“…It therefore seems unlikely that enhancement of agonist-evoked intracellular Ca¥ release by acetate could fully explain the prolonged elevation in secretion in rabbit mandibular glands. In perfused rabbit mandibular glands, the weak base NHÚCl had dramatic inhibitory effects upon ACh-evoked fluid secretion (Lau, Donohue & Case, 1996). Even at concentrations as low as 0•5 mÒ, NHÚCl totally inhibited fluid secretion.…”
Section: Fluid Secretionmentioning
confidence: 93%
“…Unfortunately, it is difficult to distinguish these two possibilities experimentally, and the evidence in the present study is broadly consistent with either hypothesis. Relevance to acinar cell electrolyte secretion Weak acids and bases have been reported to alter the rate of fluid and electrolyte transport in a diverse range of epithelia exocrine glands weak acids have been reported to stimulate salivary fluid secretion (Novak & Young 1989), while NH4Cl has dramatic inhibitory effects, even at the very low concentration of 0 5 mm (Lau, Donohue & Case, 1996). Furthermore, as discussed above, weak bases have been found to alter both the rate of tracer ion fluxes (Seagrave et al 1992a, b) and the activity of membrane ion channels (Hayashi et al 1992; in acinar cells.…”
Section: Ca2+ Entrymentioning
confidence: 99%